Peran Caregiver Dalam Mengenalkan Anggota Tubuh Pada Individu Autistik Usia Prasekolah - Diah Retno Anggraini (Universitas Indraprasta PGRI Jakarta, 2018)
It is estimated that around 40,000-70,000 children become victims of sexual exploitation and about 100,000 children are trafficked each year. It clearly proves the children’s lack of knowledge about sex education they should have gained in their first year from their caregivers, in this case their mothers. Entering the age of 1-2, children’s curiosity and ability to speak and to remember begin to increase quite well. This is the right time to continuously enrich their vocabularies and hone their ability to remember and speak by introducing body parts like hair, nose, knees, heels, and so on. Autism is a term used to describe a type of pervasive disorder in a child resulting in a disturbance or delay in cognition, language, behavior, communication and social interaction. Providing education and understanding is a special challenge for caregivers. This study illustrates how the role performed and displayed by the caregiver (mother) of autistic individuals in introducing the parts of body. The method used in the study is a qualitative method with case study approach by conducting observation and interview with the caregiver of autistic children. The result of the study indicates that the full role of caregiver (mother) produces autistic children with independent behavior. They can understand their body parts, maintain the hygiene of body parts and understand what body parts that may be touched and not